Contribution of microbial communities to flavors of Pixian Douban fermented in the closed system of multi-scale temperature and flow fields. (1st January 2023) - Ye, Xiaoqing; Liu, Yan; Peng, Changbo; Guan, Xi; Liu, Yi; Che, Zhenming; Lin, Hongbin; Min, Xu; Zhu, Qi; Ding, Wenwu
Abstract: In this study, Pixian Douban (PXDB) was produced in a closed system of multi-scale temperature and flow fields constructed with the materials of pseudoplastic fluid in a gradient steady-state temperature field. The flavors and microorganisms of PXDB in the MTFF were compared with those in the traditional process with original materials (TPOM) and the traditional process with materials of pseudoplastic fluid (TPPF). The contents of organic acids, free amino acids and flavors in the MTFF were higher than those in the TPPF and TPOM. Chitinophagaceae_Unclassified and Bradyrhizobium_Unclassified were the predominant bacteria while Phyllachora sp . UB03986 and Rhizopus oryzae were identified as the core fungi at the species levels in the processes. The correlation analysis showed that 26 bacterial and 6 fungal were significantly correlated with the flavors. The results indicated that the closed system of MTFF could improve the product quality and was helpful to realize the controllable PXDB production. Highlights: A system of multi-scale temperature and flow fields was designed in this study. The contents of the flavor substances in the system were the highest. The flavor characteristics were more stable during the fermentation in the system. The growth of dominant microbes was strongly enhanced in the system.